Violent Behavior: Crime and Criminological Aspect - Igrački, Jasmina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
The study of violent behaviour, as one of the most intriguing phenomena of modern civilisation, has a special significance in comprehending, interpreting, and understanding human behaviour and the social environment. Violence is characterised by, as a rule, the use of force, and it is the most frequent medium for the achievement of a goal. In criminal law, violence is an incriminating human behaviour that hurts or endangers legally protected goods, while using force or a serious threat. In this paper, two criminal offences of violent behaviour have been analysed: violent behaviour (act 344. KZ SR) and violent behaviour at sports events or public meetings (act 344a. KZ SR).